Guia de plantas medicinais do Quilombo São José de Icatu (Mocajuba, Pará, Brasil) - CONCEIÇÃO, Maria do Rosário da Silva (2024)
The object of the work was to present a didactic product composed of a digital illustrated guide, to document the knowledge about the medicinal plants grown in the backyards of the Community of São José do Icatu, as a didactic resource for the discipline Ethnobotany (Higher Education) and for the use and dissemination of this knowledge within the community in question. Through interviews and guided tours of the backyards of the houses, the photographic record of the plant species used for medicinal purposes was made. From these data, the digital illustrated guide was elaborated documenting the photographic image, the scientific and vernacular name of each species, as well as its synonyms, as well as the description, forms of use and distribution of the species in Brazil. The digital book consists of 58 pages, with the illustration of 30 medicinal plants belonging to 18 botanical families. Among the species recorded, one in particular caught our attention: Aeollanthus suaveolens Mart ex. Spreng (Catinga, Catinga-de-mulata); Because it is a kind of African origin introduced with colonization and that has a very strong symbolism in Afro-Brazilian culture.